Transcranial Direct Current Stimulation Targeting the Entire Motor Network Does Not Increase Corticospinal Excitability - Van der Cruijsen, Joris; Jonker, Zeb D.; Andrinopoulou, Eleni-Rosalina; Wijngaarden, Jessica E.; Tangkau, Ditte A.; Tulen, Joke H. M.; Frens, Maarten A.; Ribbers, Gerard M.; Selles, Ruud W. (Frontiers in Human Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) over the contralateral primary motor cortex of the target muscle (conventional tDCS) has been described to enhance corticospinal excitability, as measured with transcranial magnetic stimulation. Recently, tDCS targeting the brain regions functionally connected to the contralateral primary motor cortex (motor network tDCS) was reported to enhance corticospinal excitability more than conventional tDCS. We compared the effects of motor network tDCS, 2 mA conventional tDCS, and sham tDCS on corticospinal excitability in 21 healthy participants in a randomized, single-blind within-subject study design. We applied tDCS for 12 minutes and measured corticospinal excitability with TMS before tDCS and at 0, 15, 30, 45, and 60 minutes after tDCS. Statistical analysis showed that neither motor network tDCS nor conventional tDCS significantly increased corticospinal excitability relative to sham stimulation. Furthermore, the results did not provide evidence for superiority of motor network tDCS over conventional tDCS. Motor network tDCS seems equally susceptible to the sources of intersubject and intrasubject variability previously observed in response to conventional tDCS.